1979
DOI: 10.1038/icb.1979.54
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibition of Malignant Cell Growth by Ketone Bodies

Abstract: Summary, The effect of ketone bodies on ihe growth, in culture, of transformed lymphoblasts (Raji cells) was investigated. Cell growth was inhibited and this efTect was reversible, non-toxic, and proportional to the concentmtion of D-j^-hydroxybutyrate up to 20mM. The total glucose utilisation and the total lactate production were reduced in proportion to the inhibition of cell proliferaiion. D-^-hydroxybutyrate was not metabolised by the eells. Other glycolytic inhibitors and chemical analogues of f5-^-hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
74
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 8 publications
(14 reference statements)
7
74
0
Order By: Relevance
“…These findings give support for parenteral nutrition studies in the wasted cancer patient where some consideration is now being given to the parenteral infusion of lipid, rather than glucose, with potential benefits in the maintenance of body weight and lack of tumour progression (Magee et al, 1979;Conyers et al, 1979b;Buzby et al, 1980;Brennan, 1981).…”
Section: Blood and Liver Metabolitesmentioning
confidence: 85%
See 4 more Smart Citations
“…These findings give support for parenteral nutrition studies in the wasted cancer patient where some consideration is now being given to the parenteral infusion of lipid, rather than glucose, with potential benefits in the maintenance of body weight and lack of tumour progression (Magee et al, 1979;Conyers et al, 1979b;Buzby et al, 1980;Brennan, 1981).…”
Section: Blood and Liver Metabolitesmentioning
confidence: 85%
“…In other studies with these mice, increased ketonaemia was observed in both TB and NTB mice when fed either medium-or long-chain tryglyceride (Magee et al, 1979;Carman et al, 1981), which suggests that the ketogenic capacity of the liver in this model is not decreased by the presence of the tumour. PQ present study precluded the assessment of circulating fatty acid concentrations.…”
Section: Blood and Liver Metabolitesmentioning
confidence: 97%
See 3 more Smart Citations